Sistem Informasi Reminder Payment kepada Penyewa Apartemen melalui Kanal Informasi - Steven Winata; Francka Sakti Lee (Jurnal Algoritma, 2026)
The manual management of rent payments often leads to delays in sending billing information and difficulties in monitoring tenants’ payment status. This study designs a Payment Reminder Information System for apartment tenants via a web-based information channel, assisting in the monitoring of bills and payments and providing payment reminders in a more structured manner, using the Waterfall method, which includes the stages of planning, analysis, design, implementation, and testing. Unified Modeling Language (UML) was used in the system’s design. The developed system offers features for invoice management, payment information delivery, payment proof upload, payment validation, and the sending of payment reminders via channels such as WhatsApp, email, and a web-based information system. The research results indicate that the system can help administrators monitor tenant payments in a more structured manner and facilitate the delivery of payment information, thereby reducing payment delays.